Identification and phylogenetic study of a new species of Lulesia (Entolomataceae, Agaricales) from China, based on morphological and multi-gene data - Han, Meiling; Jiang, Shuhui; Liu, Yiman; Zhao, Xiya; Li, Ruimin; Shui, Wanrui; Zhang, Wenbo; Zhang, Yujiao; Liu, Wenhui; Zhao, Xuan; Jiao, Zhiyin; Wang, Lian; et al. (Phytotaxa, 2026)
A new Lulesia species, namely Lulesia hebeiensis, collected from northern China, is described and illustrated based on morphological characteristics and molecular evidence. It is characterized by pale cream, pale olivaceous buff to light vinaceous grey pileus, pale cream to clay-buff stipe, white to cream decurrent lamellae, a negative reaction to KOH, regular lamellae trama, subglobose to broadly ellipsoid angular basidiospores (4.7–5.4 × 3.9–4.5 μm), and the absence of clamp connections. Molecular phylogeny inferred from the combined 5-gene dataset (ITS + nLSU + RPB2 + TEF1 + ATP6) showed that samples of L. hebeiensis formed a distinctive lineage in L. subg. Lulesia, and it is nested as a sister group to L. densifolia.